2015
DOI: 10.1002/ab.21586
|View full text |Cite
|
Sign up to set email alerts
|

The association between childhood maltreatment, mental health problems, and aggression in justice‐involved boys

Abstract: The link between childhood maltreatment and adolescent aggression is well documented; yet, studies examining potential mechanisms that explain this association are limited. In the present study, we tested the association between childhood maltreatment and adolescent aggression in boys in juvenile justice facilities (N = 767) and examined the contribution of mental health problems to this relationship. Data on childhood maltreatment, mental health problems, and aggression were collected by means of self-report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 67 publications
4
25
0
Order By: Relevance
“…Consistent with previous studies showing a close relationship between childhood maltreatment and aggression ( Connor et al, 2004 ; Chen et al, 2012 ; Kolla et al, 2013 ; Hoeve et al, 2015 ), we also find a significant positive correlation between the two factors. More importantly, the results not only support the relationship between them but also demonstrate the specific way in which childhood maltreatment affects aggression.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with previous studies showing a close relationship between childhood maltreatment and aggression ( Connor et al, 2004 ; Chen et al, 2012 ; Kolla et al, 2013 ; Hoeve et al, 2015 ), we also find a significant positive correlation between the two factors. More importantly, the results not only support the relationship between them but also demonstrate the specific way in which childhood maltreatment affects aggression.…”
Section: Discussionsupporting
confidence: 92%
“…Child maltreatment is broadly defined as acts of commission, words or overt actions that cause harm (i.e., emotional, physical, and sexual abuse) and acts of omission, failure to provide for a child’s basic needs or protect a child from harm (i.e., emotional and physical neglect) ( Leeb et al, 2008 ). Numerous studies find a strong relationship between childhood maltreatment and aggression ( Chen et al, 2012 ; Hoeve et al, 2015 ). Maltreated children are found to show more aggressive behaviors reported by their peers, their teachers, their counselors, and themselves ( Shields and Cicchetti, 1998 ; Bolger and Patterson, 2001 ; Finzi et al, 2001 ; Weder et al, 2009 ; Alink et al, 2012 ; Shackman and Pollak, 2014 ; Dackis et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Maltreatment of a child includes sexual abuse (SA), physical abuse (PA), emotional abuse (EA) and neglect (Miller et al, 2013 ). Such maltreatment is known to be a risk factor for adolescent aggressive behavior (Ford et al, 2012 ; Hoeve et al, 2015 ) and is associated with suicidal behavior (Carli et al, 2011 ), delinquency and violent criminal behavior in adults (Miller et al, 2013 ; Carli et al, 2014 ) as well as other psychological dysfunctional attributes in adulthood (Boyda and McFeeter, 2015 ). First, a lot of work has shown that emotional and mental health outcomes for adolescents who have experienced childhood abuse are worse than for those who did not.…”
Section: Introductionmentioning
confidence: 99%
“…For adolescents, a number of studies have found evidence that CM predicts a higher risk of involvement in a variety of aggressive, antisocial, or violent behaviors (e.g. Maas et al ., 2008; Wilson et al ., 2009; Hoeve et al ., 2015). In this research, both multi-type maltreatment and physical abuse have been regarded as the most toxic types of adversity with regard to precipitating juvenile delinquency (Maas et al ., 2008).…”
Section: Introductionmentioning
confidence: 99%